2014
DOI: 10.1093/jnci/djt369
|View full text |Cite
|
Sign up to set email alerts
|

TGF- : Duality of Function Between Tumor Prevention and Carcinogenesis

Abstract: Several mechanisms underlying tumor progression have remained elusive, particularly in relation to transforming growth factor beta (TGF-β). Although TGF-β initially inhibits epithelial growth, it appears to promote the progression of advanced tumors. Defects in normal TGF-β pathways partially explain this paradox, which can lead to a cascade of downstream events that drive multiple oncogenic pathways, manifesting as several key features of tumorigenesis (uncontrolled proliferation, loss of apoptosis, epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
411
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(437 citation statements)
references
References 198 publications
(278 reference statements)
6
411
1
6
Order By: Relevance
“…As previously reported, TGF-β induces EMT in various types of cancer cells, increasing their invasion and migration and resulting in enhanced metastasis (22,23,29). The present study demonstrated that MCF-7 and A549 human cancer cells may be induced by TGF-β to undergo a stimulated EMT, reducing E-cadherin expression level in cancer cells and increasing their invasiveness and migration.…”
Section: Discussionsupporting
confidence: 82%
“…As previously reported, TGF-β induces EMT in various types of cancer cells, increasing their invasion and migration and resulting in enhanced metastasis (22,23,29). The present study demonstrated that MCF-7 and A549 human cancer cells may be induced by TGF-β to undergo a stimulated EMT, reducing E-cadherin expression level in cancer cells and increasing their invasiveness and migration.…”
Section: Discussionsupporting
confidence: 82%
“…57 Thus, we have the following equations describing the dynamics of the two cancer cell populations:…”
mentioning
confidence: 99%
“…9 Among these ECM proteins, the transforming growth factor-β (TGF-β) acts in PDA as a potent tumor suppressor and tumor promoter in a contextdependent manner. 10,11 In PDA, TGF-β impacts are driven by Sma and Mad-related protein (SMAD)2/3/4 pathway activation/ inactivation as well as by SMAD-independent pathways, that is, phosphatidylinositol-3 kinase (PI3K)/protein kinase B (Akt) pathway, JNK/p38 non-Smad pathway or mitogen-activated protein kinase (MAPK) pathway. 12,13 Overall, PDA studies support the notion that disabling TGF-β/Smad4 signaling pathway may be a critical event in pancreatic cancer progression, and open up a specific route toward the design of biomarkers as well as adjuvant therapies for this pathology.…”
mentioning
confidence: 99%